Positive Effects on Alfalfa Productivity and Soil Nutrient Status in Coastal Wetlands Driven by Biochar and Microorganisms Mixtures - Cui, Qian; Xia, Jiangbao; Peng, Ling; Zhao, Ximei; Qu, Fanzhu (Frontiers in Ecology and Evolution, 2022)
Biochar application in reclaiming degraded soils and improving plant productivity have been recognized as a promising technology. Yet, the impacts of biochar and mixtures with compound effective microorganisms (CEM) on alfalfa growth and soil quality in coastal wetlands are poorly understood. A greenhouse experiment was set to systematically reveal the impacts of biochar and biochar combined with CEM on alfalfa growth traits, nutrient uptake, biomass, soil quality and enzyme activities. Eight treatments were included: 1) control (CK-CEM), 2) 10 g /kg biochar (B10-CEM); 3) 20 g/kg biochar (B20-CEM); 4) 30 g/kg biochar (B30-CEM), 5) CEM without biochar (CK+CEM); 6) 10 g/kg biochar with CEM (B10+CEM), 7) 20 g/kg biochar with CEM (B20+CEM), 8) 30 g/kg biochar with CEM (B30+CEM). The utilization of biochar promoted seed germination, height and tissue nutrient contents of alfalfa, and the combined biochar with CEM showed greater effects. Alfalfa biomass showed the maximum value in the B20+CEM treatment, and the biomass of root, shoot, leaf in the B20+CEM treatment increased by 200%, 117.3%, 144.6%, respectively, relative to the CK-CEM treatment. Alfalfa yield in the CK+CEM, B10+CEM, B20+CEM, B30+CEM treatments was 71.91%, 84.11%, 138.5% and 120.5% higher than those in the CK-CEM treatment. The use of biochar and CEM decreased soil salinity and elevated soil nutrient content effectively. Biochar elevated soil organic carbon (SOC) and microbial biomass carbon (MBC), NH4+, NO3- and enzymatic activities, and the positive impacts of biochar combined with CEM were additive. The combined addition of 20 g/kg biochar with CEM showed the pronounced improvement effects on improving soil fertility and nutrient availability as well as soil enzyme activities. Path analysis indicated that the application of biochar mixture with CEM promoted alfalfa biomass by regulating plant nutrient uptake, soil quality (soil nitrogen, SOC, MBC, NH4+, NO3-) and soil enzymatic activities (sucrase, urease and alkaline phosphatases). Thus, incorporation of suitable biochar and CEM can serve as an effective measure to promote alfalfa productivity and restore coastal wetlands soils.